2018
DOI: 10.3390/su10061954
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship among University–Research Institute–Industry Innovations Using a Coupling Coordination Degree Model

Abstract: Abstract:With the socio-economic development in China, the central government pays more and more attention to innovations. Universities, research institutes, and industries (URI) are the main bodies of innovation. Therefore, in order to perform sustainable development of innovation, it is essential for Chinese policy makers to better understand the relationship among URI innovations. In this paper, indicators for evaluating URI innovations are collected, which are classified into three subsystems. Utilizing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Here, α and β are the coefficients. After referring the existing research and the characters of the two subsystems, here we determine α � β � 0.5 [66]:…”
Section: Calculation Of the Subsystems' Development Degreementioning
confidence: 99%
“…Here, α and β are the coefficients. After referring the existing research and the characters of the two subsystems, here we determine α � β � 0.5 [66]:…”
Section: Calculation Of the Subsystems' Development Degreementioning
confidence: 99%
“…A number of studies have been carried out with a diverse range of work that refers to urban sustainability in China. Provinces and cities such as Beijing [89], Shanghai [65,77], Guangxi [37] and urban agglomerations [39] were taken as research areas to analyze urban sustainability issues. It can be seen that different indicators systems were developed for different regions.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of coupling stems from the physics [74][75][76]. Coupling describes the phenomenon by which two or more systems influence each other through interactive mechanisms [77][78][79][80]. So, coupling can be used to identify the relationship among the five aspects of urbanization.…”
Section: The Coupling Coordination Degree Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Through research and analysis of the principle of coupling between industries, economists have found the optimal combination of interactions between two or more industries, which enables them to promote each other, support each other, and coordinate development. In summary, its application in industrial economic research mainly includes the following aspects: research on the overall development level of industry [25][26][27], construction and application of the coupling coordination degree model [28][29][30][31], and prediction studies measuring degrees of coupling coordination [25,28]. The coupling between the agriculture and PV industries is based on systems theory.…”
Section: Introductionmentioning
confidence: 99%